The Application of a Fed Batch Reactor for Composting of Vegetable and Fruit Wastes.. - Jolanun, B.; Tripetchkul, S.; Chiemchaisri, C.; Chaiprasert, P.; Towprayoon, S. (Science & Technology Asia, 2015)
-